Fabrication of TiO2 nanotubes on Ti spheres using bipolar electrochemistry - Sopha, Hanna; Hromádko, Luděk; Motola, Martin; Macák, Jan (Elsevier, 2020)
In this work, the anodization of Ti spheres using bipolar electrochemistry is reported for the first time. TiO2 nanotubes were found over the entire surface area of the Ti spheres when a square-wave potential was employed. The TiO2 nanotubes were ∼77 nm in inner diameter and had a thickness of ∼2 µm on the extremities of the Ti spheres. Due to their increased surface area, the Ti spheres covered with TiO2 nanotubes had a rate constant for the photocatalytic degradation of methylene blue which was approximately 2.15 times higher than that of non-anodized Ti spheres with a thin thermal oxide layer.
Keywords: TiO2 nanotube layers; Ti spheres; Bipolar Electrochemistry; Photocatalysis